Orange-fleshed sweetpotato has become a common dish in SUSTAIN Kenya intervention sites - International Potato Center (2017)
By the end of year 4, the project has reached 90% of its five-year direct beneficiary target, providing households with improved orange-fleshed sweetpotato (OFSP) planting material and nutrition education. This far, OFSP has moved in the target areas from being not utilized at all in most households to being consumed at least twice a week when the roots are in season. Behavior change is starting to happen and now OFSP is part of complementary feeding practices for young children, due to a strong collaborative effort with the Ministry of Health.